Assessing the status of Australia's fish stocks relative to target objectives. (February 2020) - Hill, Nicholas J.; Gardner, Caleb; Haddon, Malcolm; Hartmann, Klaas; Little, L. Richard; Lyle, Jeremy M.; Moore, Bradley R.
Abstract: Communicating the performance of commercial fish stocks is a fundamental role of fisheries management. This is often undertaken by reporting stock status relative to limit reference points (LRP). Reporting against LRP is effective in drawing attention to stocks that are overfished but does not identify fisheries where performance could be improved by shifting stocks closer to target reference points (TRP), that is, benefit can be foregone despite stocks being fished sustainably. This study examined the performance of Australian fish stocks against a TRP of 40–60% of unfished biomass, the level at which economic performance is generally optimised. Stocks examined were drawn from the 2016 Status of Australian Fish Stocks report, which is designed to report on stock status relative to LRP at a national level. Only stocks with an estimate of biomass or status relative to explicitly defined reference points were considered. Of 123 stocks evaluated, 41 (33%) were at target biomass levels, 28% were above and 39% below. This result, in combination with the major output of the 2016 SAFS report, shows that although most Australian stocks are not overfished, many are outside levels that would deliver greatest benefits. While maintaining all stocks at target levels may be impractical given the dynamic nature of fisheries, failing to maximise the number of stocks at target levels reflects lost ecological, economic and social potential. Assessing stocks relative to TRP in addition to LRP would highlight opportunities for improving fisheries while still addressing the fundamental requirement of preventing stock depletion.